Resistivity Recovery in Fe and FeCr alloys - Gómez-Ferrer, Begoña (SpringerBriefs in Applied Sciences and Technology, 2016)
This book covers the Resistivity Recovery (RR) technique, underlying its physical principles, performance and problematic. A concise review on the state of the art is provided, showing the advances in radiation modelling, linking both experimental and theoretical fields. The reader will find a data compilation and comparison of up-to-date results obtained from the European Fusion Development Agreement model alloys. .